Pengaruh Kombinasi Metformin dan Ekstrak Kunyit terhadap Kadar High Density Lipoprotein, Interleukin-6 dan Tumor Necrosis Factor-a - Dinanti, Fathia Kesuma; Mulyani, Sri Priyantini; -, Chodidjah - (Jurnal Kesehatan Andalas, 2022)
A  decrease in high-density lipoprotein (HDL) happens in type 2 diabetes mellitus. The cytokines TNFa and IL-6 are proinflammatory cytokines that are elevated in the blood in many patients with DM. Turmeric is one of the natural ingredients with antioxidant, anti-cholesterol, and anti-inflammatory properties through its active substance, curcumin. Objective: To prove the effectiveness of the combination of metformin and turmeric extract on HDL levels, TNFa levels, and IL-6 levels in Streptozotocin-Nicotinamide-induced Wistar rats. Methods: The study used a post-test-only controlled group design. The subjects were 24 male Wistar rats which were randomly divided into four groups, namely K1, K2, P1, and P2. The whole group was a type 2 DM model induced by streptozotocin-nicotinamide. Group K2 was given metformin 45mg/KgBW/day, group P1 was given turmeric extract at a dose of 200 mg/KgBW/day, and group P2 was given a combination of metformin and turmeric extract. On day 15, blood was drawn for HDL, IL-6, and TNFa examination. The data were analyzed using the one-way Anova test. Results: The mean HDL level in the P2 group (72,4±33,31) was the highest compared to the other three groups. The lowest mean TNFa level among the four groups was the P2 group (7,56±0,44). The lowest mean levels of IL-6 were obtained in the P2 group (58,82±2,15). One-way Anova test on HDL, IL-6, and TNFa levels showed a significant difference between groups with p-value = 0.000. Conclusion: The combination of metformin and turmeric extract can increase HDL levels and reduce IL-6 levels and TNFa levels better than giving metformin or turmeric extract alone.Keywords:  turmeric extract, HDL, IL-6, TNFa